Smart Education Tutoring Strategy to Increase Students’ Learning Motivation in Post-Pandemic - Ardani, Anisa Dewi; Liestyasari, Siany Indria; Trinugraha, Yosafat Hermawan (Lembaga Penelitian dan Pendidikan Mandala, 2023)
The Covid-19 pandemic has changed the educational landscape around the world, forcing schools and educational institutions to shift from offline to online and back again. This research explores the strategies implemented by smart education tutoring in an effort to increase student learning motivation after the pandemic using a qualitative descriptive approach with case study research. The sampling technique used purposive sampling with a total of 7 informants consisting of owners and tutors of Smart Education tutoring. The strategies discussed include using technology-based learning media, building pleasant relationships with students, providing encouragement, providing rewards in the form of prizes, grades and praise, and strengthening collaboration with students' parents. The research results show that these strategies have been successful in increasing students' learning motivation which has decreased. This research uses structural functional theory by Talcott Parsons with the four functions of AGIL, namely adaptation, goal achievement, integration, and pattern maintenance, to analyze the role of tutoring in responding to changes in the education system. The results underline the important role of tutoring in helping students overcome learning difficulties and maintaining their motivation in learning. This research provides valuable insights for tutoring and other educational institutions seeking to address post-pandemic educational challenges.